Diagnosis and Treatment of an Undifferentiated Embryonal Sarcoma of the Liver in a 37-Week Pregnant Woman: A Case Report - Hung TM; Son TQ; Phuong TT; Minh HV (Dove Medical Press, 2021)
Tran Manh Hung,1 Tran Que Son,1,2 Tran Thi Phuong,3 Hoang Van Minh4 1Department of Surgery, Bach Mai Hospital, Hanoi, Vietnam; 2Hanoi Medical University, Hanoi, Vietnam; 3Department of Epidemiology, Thai Binh University of Medicine and Pharmacy, Thaibinh, Vietnam; 4Hanoi University of Public Health, Hanoi, VietnamCorrespondence: Tran Manh HungDepartment of Surgery, Bach Mai Hospital, Hanoi, VietnamEmail tranmanhhungngoaibm@gmail.comPurpose: Undifferentiated embryonal sarcoma of the liver (UESL) is a rare malignant lesion in adults. Here, we present an extremely rare case of UESL in a pregnant woman. However, this was the first case, wherein one surgery covered all the procedures needed to be performed, including delivery of the neonate, hysterectomy, and resection of the left liver lobe to ensure the safety of both the mother and the newborn.Case Presentation: A 32-year-old woman at 37-weeks age of gestation was admitted at Bach Mai Hospital (Hanoi, Vietnam) due to epigastric pain, chest pain, and breathing difficulty. Blood tests showed an increased total alpha-fetoprotein level of 1085 ng/mL. Fetal ultrasound showed a fetal heart rate of 127 beats/minute, biparietal diameter of 92 mm, femur length of 70 mm, and fetal weight of 3287 g. Magnetic resonance imaging indicated a large tumor (12 × 14 × 18 mm) in the left liver, with organ signals increased on T2-weighted and decreased on T1-weighted. The mass was lobulated, developed along a downward pattern, and did not invade the portal vein. The surgeries performed were cesarean section, hysterectomy due to the inelasticity of the uterus, and left hepatectomy to ensure the safety of both the mother and newborn. The operation was performed safely and without any complications, and the patient was discharged from the hospital after 10 days.Conclusion: This case report with distinct characteristics has been the first case ever reported in Vietnam, as well as in the literature. We believe that this case report will be useful for the clinical evidence pool and for educational purposes.Keywords: hepatic tumor, undifferentiated embryonal sarcoma, hepatic resection, cesarean section, hysterectomy, case report